Formulation of Microemulsion of Cayenne Pepper (Capsicum Frutescens L.) Ethanol Extract and Hair Growth Activity Test - Anggraini, Deni; Sandi, Nofri Hendri; Djohari, Meiriza (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Cayenne pepper contains capsaicin, which exhibits properties that promote hair growth. Microemulsion is an oil and water dispersion system with a particle size of 10-200 nm which can be used topically as a drug delivery system through the scalp to stimulate hair growth. The microemulsion was made with olive oil and tween 80 as surfactants and stirred using a magnetic stirrer at 1000 rpm for 3 minutes. The ethanol extract of cayenne pepper was prepared in microemulsions at three different concentrations: 0.1%, 0.2%, and 0.3%. Microemulsion tests included organoleptic tests, specific gravity, pH, viscosity, freezing and thawing stability tests, and hair growth activity tests on rabbits. The results showed that the microemulsion of cayenne pepper ethanol extract at concentrations of 0.1%, 0.2%, and 0.3% was quite stable with a clear appearance and a particle size ranging from 27.7 nm to 167.8 nm. The microemulsion of cayenne pepper ethanol extract at a concentration of 0.2% was the most effective in enhancing hair growth, achieving a hair growth length of 1.27 over a 30-day period. A two-way ANOVA statistical test showed that the hair length of rabbits using microemulsion was significantly different from the hair length of negative control animals at p<0.05.